The Transition Economies After Ten Years - Fischer, Stanley; Sahay, Ratna (Washington, D.C. : International Monetary Fund, 2000)
This paper summarizes the macroeconomic performance of the transition economies. We first review the initial conditions confronting these economies, the reform strategy that was proposed, and the associated controversies that arose a decade ago. We then account for the widely different outcomes, highlighting the role of exogenous factors and the macroeconomic and structural policies adopted by the countries. We find that both stabilization policies and structural reforms, particularly privatization, contribute to growth. We also conclude that the faster is the speed of reforms, the quicker is the recovery and the higher is growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet